SIFAT SENSORIS PEMPEK IKAN SARDEN (Sardina pilchardus) DENGAN PENAMBAHAN ISOLATE SOY PROTEIN - Ade Vera Yani; Idealistuti Idealistuti; Muhammad Agus Burliansyah; Nico Syahputra (Fakultas Pertanian Universitas Riau, 2025)
This study aims to determine the effect of the addition of soy protein isolate on the sensory properties of sardine fish pempek. This study was conducted at the Laboratory of the Faculty of Agriculture, Muhammadiyah University of Palembang. The method used is an experimental method with a Randomized Block Design (RAK) arranged in a Non-Factorial manner with five treatments, namely P0 (sardine fish pempek without the addition of soy protein isolate), P1 (sardine fish pempek + 2% soy protein isolate), P2 (sardine fish pempek + 4% soy protein isolate), P3 (sardine fish pempek + 6% soy protein isolate), P4 (sardine fish pempek + 8% soy protein isolate). The parameters observed include sensory analysis (color, aroma, taste, and elasticity). The results showed that the addition of soy protein isolate significantly affected the color, aroma, taste, and elasticity. The most preferred treatment was P4 (sardine fish pempek with the addition of 8% soy protein isolate) with average characteristic values of color (4.04), aroma (3.44), taste (3.76), and chewiness (3.56).